Policing history. The official discourse and organizational memory of the Royal Ulster Constabulary - Mulcahy, Aogán (The British journal of criminology, 2000)
This paper considers the nature and impact of the organizational memories that form the core of the Royal Ulster Constabulary's (RUC) official discourse. As the ongoing Northern Ireland peace process developed, the issue of police reform moved to the forefront of the political agenda. Reform proponents who drew on historical controversies to press for specific changes were frequently dismissed by the RUC as hatemongers who were locked in the past. While the force maintained that its focus was on the future rather than on the past, the RUC's collective identity is itself heavily reliant on specific constructions of history. This is most evident in the RUC's active celebration of the themes of sacrifice and bravery, community support, and accountability. These organizational memories underpin the force's criticism of proposals for radical reform and its denigration of reform proponents. While these memories function to legitimize the RUC in the eyes of its supporters, they also undermine the development of institutional reflexivity central to processes of political transition and conflict resolution